HISTORICITY OF ISLAMIC EDUCATION IN THE NUSANTARA - RIJAL, FAZKA KHOIRU (TAWASUT, 2023)
The development of Islamic education cannot be separated from Islam itself, including through cultural acculturation. There are various ways in the development of Islam and Islamic education in Indonesia, including through trade, marriage, education, politics, art, Sufism, all of which help and support the spread of Islamic teachings. Along with the entry of Islam, Islamic educational institutions also run and develop in order to propagate Islam in Indonesia. In this journal, the author will explain qualitatively with a descriptive method to discuss in detail and in depth the discussion of the historicity of Islamic education in Indonesia. The history of Indonesian Islamic education is essentially very closely related to the history of Indonesian Islam, the historical period of Islamic education is also contained in the history of Islam. Both are closely related and work together in guiding and spreading the religion and Islamic education. This journal will explain the history of Islamic education in Indonesia during the Islamic empire, the colonial period, and the independence period. Keywords: Historical Islamic Education, Islamic Education during the Islamic Kingdom, Colonial Period, and Independence Period